Clinical course and management of insidious adrenal crisis manifested initially as hyperpyrexia secondary to pembrolizumab: Case reports and literature review - Geng, Dandan; Wang, Yingnan; Zhang, Xin; Zhao, Chenguang; Fan, Yao; Liu, Chang; Wei, Jinmei; Huo, Bingjie; Zhao, Yang; Zhang, Fengbin; Zhang, Ruixing (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) are novel drugs with a dramatic survival benefit in patients with advanced malignancies. With the widespread use, several immune-related adverse events (irAEs) have emerged, which may be life-threatening. Herein we report two patients with adrenal crisis who received anti-programmed cell death protein 1 (PD-1) (pembrolizumab) therapy. Several reports of secondary adrenal insufficiency caused by pembrolizumab exist, including during treatment or late onset. Severe adrenal insufficiency according to the Common Terminology Criteria for Adverse Events (CTCAE) has rarely been described in the literature, since it initially manifests as high grade fever. The two male patients developed adrenal crisis that was first characterized by hyperpyrexia accompanied by abdominal symptoms. These initial manifestations confused the clinicians who misdiagnosed them as infection. Timely identification, hydrocortisone pulse therapy, and fluid resuscitation improved the patients' condition. Compliance with the standardized treatment approach and course can prevent or relieve the crisis as soon as possible. Assessment of relevant laboratory test results and patient education, including when to use stress-dose hydrocortisone and guidance on route of administration, can reduce the incidence of adrenal crisis. We report these two cases and have evaluated the literature on previously reported cases to improve our understanding of this condition and offer more scientific approach to diagnosis and treatment options.